Cooperation in large networks: an experimental approach (2007)
We present a new design of a simple public goods experiment with a large number of players, where up to 80 people in a computer lab have the possibility to connect with others in the room to induce more cooperators to contribute to the public good and overcome the social dilemma. This experimental design explores the possibility of social networks to be used and institutional devices to create the same behavioral responses we observe with small groups (e.g. commitments, social norms, reciprocity, trust, shame, guilt) that seem to induce cooperative behavior in the private provision of public goods. The results of our experiment suggest that the structure of the network affects the players' ability to communicate -and through it, their cooperation levels-, and also their willingness to engage in a more costly type of collective action, namely the endogenous creation of new links to individuals previously out of reach. Finally, the information flows in the network seem to reduce uncertainty in the players: players with more links tend to have more stable play strategies.